Teknik Relaksasi Otot Progresif Pada Pasien Kanker Payudara Preoperasi - Sumitro Adi Putra; Herawati Jaya; Eva Gustina (JKM : Jurnal Keperawatan Merdeka, 2026)
Background: : Breast cancer is one of the most common types of cancer experienced by women worldwide. A diagnosis of breast cancer often has a major psychological impact, especially when the patient is going to undergo surgery. The pre-operative period is a vulnerable period, where many patients experience high anxiety or worry due to fear of medical procedures, surgical results, and physical changes and life afterward. This study aims to evaluate the implementation of progressive muscle relaxation techniques in reducing anxiety levels among breast cancer patients in the preoperative phase. Method : Descriptive case study with a maternity nursing care approach. The case study subjects were 2 people with the same problem, namely anxiety. The location of the case study was at the Muhammadiyah Hospital in Palembang which was carried out in May 2025. Data was taken using the nursing care assessment format and then the data was presented in tabular form. Results : There was a decrease in anxiety in each patient after progressive muscle relaxation was carried out for 10 minutes. Conclusion: Implementation of progressive muscle relaxation nursing is effective in overcoming anxiety in preoperative breast cancer patients.